Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/nl104357e
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Driven Agglomeration and Growth of Single Crystal Metal Wires

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Many of the wires were observed to sprout from these agglomerated particles suggesting the particles behaved as nucleation and crystal growth centres for the newly formed wires, in a manner similar to that of VLS. It also was demonstrated that introducing ion beam lithography defined holes into the film prior to annealing made it possible to have a degree of control over the positioning and growth of the subsequently grown wires 14 . The phenomena led to the formation of 'agglomeration waves' but the physical origin was not understood at that time.…”
Section: Characteristics Of the Sedg Methodsmentioning
confidence: 99%
“…Many of the wires were observed to sprout from these agglomerated particles suggesting the particles behaved as nucleation and crystal growth centres for the newly formed wires, in a manner similar to that of VLS. It also was demonstrated that introducing ion beam lithography defined holes into the film prior to annealing made it possible to have a degree of control over the positioning and growth of the subsequently grown wires 14 . The phenomena led to the formation of 'agglomeration waves' but the physical origin was not understood at that time.…”
Section: Characteristics Of the Sedg Methodsmentioning
confidence: 99%
“…The increased aggregation of ground talc with 0.1 mm balls than with 1 mm or 2 mm balls could be related to the degree of dispersion in the aqueous solution used in the particle size analysis. The aggregation of ultrafine particles generally occurs in order to reduce the high surface energy [34,35]. The talc powders with a similar surface area and different aggregation behavior indicate that these ground talc powders have a different surface energy and/or property.…”
Section: Aggregation Of Ground Talcmentioning
confidence: 99%
“…Ge will phase separate from Au upon cooling due to the differences in their surface energies 147 and depending on the amount of Au present, a variety of structures ranging from pyramid shaped nanoislands to uniform core-shell structures can be formed, as shown in figure 8. The formation of various nanostructures (which included islands, periodic nanodisks and core-shell structures) was explained by the phase diagram 142 , with the authors controlling the atomic percentage of Au and thermal annealing above the eutectic temperature.…”
Section: The Au/ge Systemmentioning
confidence: 99%